Metafora soli w Biblii i literaturze wczesnochrześcijańskiej - Paczkowski, Mieczysław Celestyn (Vox Patrum, 2013)
The article presents the complex symbolism of salt that was strongly influenced by the rites and beliefs of the pagan and the biblical world as well as early Christian literature. The salt is an element present in every aspect of human life (food, medicine and religious cults). It played an important role in sacrifices and offerings of Old Testament. For this reason, Jesus’ use of this metaphor was extremely familiar to His followers. On the biblical bases the various allegorical motifs of salt were present in Christian authors. Metaphors associated with the salt became precise and rich. Salt was a symbolic figure of wisdom, moral cleanness and incorruptibility. God’s salt enabled one to triumph over the spiritual enemy. The Fathers taught to point others to the way of life, to show how they might be preserved from death and destruction. They pointed out how the purpose of Christian life depended on their spiritual saltiness.